Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a Taylor series problem, well more precisely a Maclaurin series.

I am trying to find convergence of: $f(x) = e^{x^3} + e^{{2x}^3}$

Okay here goes:

$$f'(x) = 3xe^{x^3} + 6x e^{{2x}^3}$$ $$f''(x) = 9x^2e^{x^3} + 3e^{x^3} + 36x^2e^{{2x}^3} + 6e^{{2x}^3}=e^{x^3}(9x^2+3) + e^{{2x}^3}(36x^2+6)$$ $$f'''(x) = (9x^2+3)(3xe^{x^3}) + 18xe^{x^3} + (36x^2 + 6)(6xe^{2x^3}) + 72xe^{2x^3}$$ $$=27xe^{x^3}(x^2 + 1) + 108xe^{2{x^3}}(2x^2 + 1)$$

Now I don't see a pattern, but I can note at $a=0$ we have:

$$f(0)=2$$ $$f'(0)=0$$ $$f''(0)=9$$ $$f'''(0)=0$$

I am not sure where this is going, or if this is the right way to attack the problem. Any advice?

share|cite|improve this question
You mis-differentiated $x^3$, that yields $3x^2$, not $3x$. The right way to attack the problem is to take the expansion of $e^z$, substitute in $z = x^3$ resp $z = 2x^3$, and add. – Daniel Fischer Jun 5 '14 at 12:34
What is the problem - finding the expansion at $x=0$? – mvw Jun 5 '14 at 12:36
@DanielFischer I can't believe that happened... But yes that second part of the comment makes sense. – Tony Jun 5 '14 at 12:36
up vote 2 down vote accepted

To supplement the other answer, here's how you would determine convergence using the ratio test:

We would like to test the convergence of the sum $$ \sum_{n=1}^\infty a_{3n} x^{3n} = \sum_{n=1}^\infty \frac{1 + 2^n}{n!}x^{3n} $$ In order to do so, we need to determine the value of $$ \limsup_{n \to \infty} \left|\frac{a_{n+1}x^{n+1}}{a_nx^n}\right| = \lim_{n \to \infty} \frac{(1 + 2^{n+1})x^{3(n+1)}}{(n+1)!} \cdot \frac{n!}{(1 + 2^n)x^{3n}} $$ Simpifying, this becomes $$ \lim_{n \to \infty} \frac{x^3}{n+1} \cdot \frac{1+2^{n+1}}{1+2^n} $$ Noting that this limit becomes zero for all $x$ and noting that $0<1$, we conclude that this sum converges for all $x$ by the ratio test.

share|cite|improve this answer

Use the familiar Maclaurin expansion for the exponential:

$$e^t=1+t+\frac{t^2}{2!}+\dots=\sum_{n=0}^\infty \frac{t^n}{n!}. $$ If you plug in $t=x^3$ you get $$e^{x^3}=\sum_{n=0}^\infty \frac{x^{3n}}{n!}. $$ If you plug in $t=2x^3$ you similarly get $$e^{2x^3}=\sum_{n=0}^\infty 2^n \frac{x^{3n}}{n!} $$ Try adding these two expansions.

share|cite|improve this answer
The sum of two series, is the series of their sum, is this correct? – Tony Jun 5 '14 at 12:38
@user151558 Correct! you should find that the coefficient of $x^{3n}$ is $\frac{1+2^n}{n!}$. – user1337 Jun 5 '14 at 12:38
How do I then find where it converges to $f(x)$? – Tony Jun 5 '14 at 12:48
Use the ratio test? This should have infinite radius of convergence, since the function is entire (in the sense of complex analysis) – Steven Gubkin Jun 5 '14 at 13:09
@StevenGubkin So it is exact at $a=0$, so at $n=1$? – Tony Jun 5 '14 at 13:10

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.